An empirical study on the relationship between logistics performance and education - Yildiz, Turkay (Business, Management and Economics Engineering, 2015)
Logistics occupations require skills that involve blue- and white-collar activities and different levels of educational skills. With the increase in global trade and competition, the varying skills necessary for different parts of the logistics sector have attracted attention. In this regard, this empirical study examines the relationship between logistics performance indicators and education assessment scores and identifies associations. The presented results, by using canonical correlation analysis, indicate that certain education assessment scores contribute more to improving logistics performance than do other variables. The variables that influence logistics performance are also highlighted.